The use of MEMRI for monitoring central nervous system activity during intact insect walking. (July 2018) - Knebel, Daniel; Assaf, Yaniv; Ayali, Amir
Graphical abstract: Highlights: Manganese enhanced magnetic resonance imaging (MEMRI) was customized for locusts. MEMRI allowed monitoring activity in multiple ganglia of walking locusts in vivo. Prothoracic and subesophageal ganglia were active in walking locusts. Abstract: Background: Monitoring neuronal activity in the intact behaving animal is most desired in neuroethological research, yet it is rarely straightforward or even feasible. Here we present the use of manganese enhanced magnetic resonance imaging (MEMRI), a technique allowing monitoring the activity of an animal's nervous system during specific behavioral patterns. Using MEMRI we were able to show activity in different ganglia of the central nervous system of intact locusts during walking. Results: We injected two groups of locusts with manganese, which serves as a magnetic contrast agent. One group was forced to walk on a treadmill for two hours, while the other was immobilized and served as a control. Subsequently, all animals were scanned in a T1 MRI protocol, and the accumulation of manganese in the neuronal tissues that were active during walking was demonstrated by comparing the scans of the two groups. Two neuronal sites showed significantly higher T1 signal in the walking locusts compared to the immobilized ones: the prothoracic ganglion, which locally controls the front legs, and the subesophageal ganglion, a head ganglion which takes part in initiation and maintenance of walking. Conclusion: MEMRI is a potent, non-invasive technique for monitoring neuronal activity in intact locusts, and arthropods in general. Specifically, it provides a promising way for revealing the role of central and high-order neuronal structures in motor behaviors such as walking.